The United States educational system - Suriñach Fernández, David (Avances en Supervisión Educativa, 2017)
The United States educational system is very complex. Due to the fact a big number of agents take play of its regulation, the differences between the education from one State compared to the education from another, or even between school districts, might be considerable. The last two largest federal education initiatives, No Child Left Behind and Race to the Top, have had a huge impact on the American education system. The escalation of the standardized test throughout the whole country as a system to be accountable for has made States and school districts to put all their efforts and resources on passing these tests.
Keywords: education system; no child left behind; race to the top; standardized tests; evaluation; curriculum; principal and educational supervision